The visual feedback training effect of the walking abilities to improve quality of life of stroke patients: a systematic review - Maratis, Jerry; Asmirajanti, Mira (Universitas Gadjah Mada, 2024)
Purpose: Stroke can cause problems with balance and gait ability. This research was conducted to describe the effectiveness of visual feedback training as an exercise method for stroke patients in training balance and gait abilities. Methods: A systematic review was conducted on articles published between 2019 and 2023 examining visual cue training for stroke patients. Results: Six relevant studies reviewed the benefits of visual feedback training on balance and gait ability, including benefits on recumbent stepping and improving the quality of post-stroke patients. Conclusion: Exercise is needed to improve post-stroke patients' balance and gait. The development of training techniques for post-stroke patients, one of which is visual feedback training, still needs to be carried out.